“Here, You Try Something”: Shifting Positioning and Engineering Engagement in a Fifth-Grade Classroom. - Miel, Karen. (Tufts Archival Research Center, 2018)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Education. Abstract: Students’ interactional positions entwine with their learning and engagement in engineering. Classroom studies suggest that students’ positions influence their engagement and opportunities to learn in a variety of disciplines. This study explores the intersections of students’ positions with their engineering engagement. Within the context of a university-led outreach program in a fifth-grade classroom, I consider shifts in two students’ engineering positions and corresponding shifts in their engineering engagement. Positioning can impact students’ learning by influencing their enactment of practices of a discipline; students’ positions shape what students expect and are expected to do in their classrooms and thus influence what students will do in learning activities. In the case presented in this paper, as one student shifted from spectator to contributor positions, she began to engage in engineering; conversely, as she shifted from contributor to spectator positions, no engagement was perceptible. This study contributes to understandings of the ways in which students are positioned and position themselves in classroom engineering activities and the affordances and limitations of this positioning. This work reinforces findings in mathematics and science education that positioning corresponds with disciplinary engagement and suggests that positioning within engineering could impact engineering learning.